Apoptosis, Autophagy, NETosis, Necroptosis, and Pyroptosis Mediated Programmed Cell Death as Targets for Innovative Therapy in Rheumatoid Arthritis - Zhao, Jianan; Jiang, Ping; Guo, Shicheng; Schrodi, Steven J.; He, Dongyi (Frontiers in Immunology, 2021)
Rheumatoid arthritis (RA) is a chronic inflammatory joint disease that can lead to clinical manifestations of systemic diseases. Its leading features include chronic synovial inflammation and degeneration of the bones and joints. In the past decades, multiple susceptibilities for rheumatoid arthritis have been identified along with the development of a remarkable variety of drugs for its treatment; which include analgesics, glucocorticoids, nonsteroidal anti-inflammatory medications (NSAIDs), disease-modifying anti-rheumatic drugs (DMARDs), and biologic response modifiers (bDMARDs). Despite the existence of many clinical treatment options, the prognosis of some patients remains poor due to complex mechanism of the disease. Programmed cell death (PCD) has been extensively studied and ascertained to be one of the essential pathological mechanisms of RA. Its dysregulation in various associated cell types contributes to the development of RA. In this review, we summarize the role of apoptosis, cell death-associated neutrophil extracellular trap formation, necroptosis, pyroptosis, and autophagy in the pathophysiology of RA to provide a theoretical reference and insightful direction to the discovery and development of novel therapeutic targets for RA.